Mentoring relationships as an enhancer of mentees’ success - Azman Ismail; Aminudin Mokhtar; Mustafa Zihni Tunca; Mehmet Genturk; Zalina Ibrahim (International Journal of Evaluation and Research in Education (IJERE), 2023)
A review of the recent studies about tertiary education student development reveals that when mentors do not practice effective relationships in mentoring programs regardless of how well designed the mentoring programs are, the goals will not be achieved. Even though many studies have been done, the role of mentoring relationships as a vital predicting variable is largely ignored in the tertiary education mentoring research literature. Hence, the current study is done to investigate the effect of mentoring relationships on mentees’ success. A cross-sectional method is used to collect survey questionnaires from undergraduate students in teaching-based universities in Sarawak. The SmartPLS is utilized to assess the quality of the study instrument and test the research hypotheses. The findings of the SmartPLS path model analysis reveal that implementation of comfortable communication and sufficient support by mentors in structured and unstructured mentoring activities has been an important antecedent of mentees’ career and leadership development. Thus, this finding may be used as significant guidelines by practitioners to understand diverse paradigms of mentoring relationship construct and planning collaborative and developmental mentoring programs to prepare mentees to become potential leaders in the 21st century of global market challenges and difficulties.